1995
DOI: 10.1039/c39950001889
|View full text |Cite
|
Sign up to set email alerts
|

Calculated structures of SAu3+and S(AuPH3)3+

Abstract: Pseudopotential ab initio calculations on SAu3+ and S(AuPH&+ closely reproduce the experimental Au-S-Au angles of monomeric S(AuPR3)3+ (PR3 = PPh3, PPri3) if both correlation and relativistic effects are included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 15 publications
6
31
0
2
Order By: Relevance
“…Two of these pairs of parameters are in the normal range observed for related sulfur-centered derivatives [27][28][29][30] (Au· · ·Au 2.990(1)-3.420(1)Å; Au-S-Au 79.5(1)-95.0(3) • ). All these Au· · ·Au and Au-S-Au values are similar to those calculated for S(AuPH 3 ) 3 + using relativistic potentials (Au· · ·Au 3.05, 3.52Å; Au-S-Au 82.3, 98.5 • ) [31].…”
Section: Sulfides and Selenidesmentioning
confidence: 82%
See 2 more Smart Citations
“…Two of these pairs of parameters are in the normal range observed for related sulfur-centered derivatives [27][28][29][30] (Au· · ·Au 2.990(1)-3.420(1)Å; Au-S-Au 79.5(1)-95.0(3) • ). All these Au· · ·Au and Au-S-Au values are similar to those calculated for S(AuPH 3 ) 3 + using relativistic potentials (Au· · ·Au 3.05, 3.52Å; Au-S-Au 82.3, 98.5 • ) [31].…”
Section: Sulfides and Selenidesmentioning
confidence: 82%
“…31 P{ 1 H} NMR data seem to indicate that the dinuclear product is a mixture of three isomers. In the crystal structure of the trinuclear product, the structure of the ligand allows the three bulky Au(C 6 F 5 ) 3 units to be coordinated at the same time, and shows very long Au-Au distances (the shortest one 7.095Å), which precludes any form of metal-metal bonding.…”
Section: Triphosphinesmentioning
confidence: 93%
See 1 more Smart Citation
“…Unfortunately, there are insuffi-nent reaches North America episodically. At Cheeka Peak Observatory on the coast of Washington State, Jaffe and co-workers (7) have observed five springtime Asian pollution events since 1997. At Tagish in the Canadian Rocky Mountains, Bailey et al (8) detected elevated levels of pesticides (lindane, chlordane, and DDT) during winter and spring and attributed them to pollution transported from continental Asia.…”
Section: Trans-pacif Ic Air Pollutionmentioning
confidence: 99%
“…The introduction of relativistic effects in more advanced calculations in the 1970s has shown that bonding between closed-shell metal atoms or ions may be strongly enhanced by these effects (56)(57)(58)(59)(60)(61)(62). Since relativistic effects have been known to be particularly strong for the heavy elements in the Periodic Table in general, and to reach a local maximum for gold in particular (6, 7), aurophilicity was accepted as a logical consequence of these contributions (5).…”
Section: Theoretical Contributionsmentioning
confidence: 99%